Polymer asphalt emulsion as well as raw material composition, preparation method and application thereof
By using specific polymer asphalt emulsion raw material compositions and preparation methods in the cold mixing and cold laying process, the problems of short mixing time, poor stability and poor water resistance in the cold mixing and cold laying process in the prior art are solved, and rapid demulsification, early strength improvement and water damage resistance improvement are achieved.
Patent Information
- Application Number
- CN202510075417.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-05-02
AI Technical Summary
In the existing cold mixing and cold laying process, the anionic polymer emulsion cannot meet the requirements of sufficient mixing operation time and road specifications. SBR and SBS modified asphalt emulsions have problems such as difficulty in demulsification and poor stability, resulting in long traffic closure time after construction and unsatisfactory water damage resistance.
The raw material composition of a polymer asphalt emulsion is adopted, including asphalt, polymerizable monomer, carboxy monomer, crosslinked monomer, functional monomer, initiator, surfactant, pH adjuster and water. Through specific preparation methods and ratios, the pH value of the emulsion and the emulsification ability of the surfactant are adjusted, and the compatibility and water resistance of the polymer and stone are improved.
It has achieved rapid demulsification of polymer asphalt emulsion, early strength improvement, reduced traffic closure time, enhanced water damage resistance and rut resistance, and expanded the scope of application of asphalt mixture.
Smart Images

Figure BDA0005246934430000071 
Figure BDA0005246934430000081 
Figure BDA0005246934430000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of asphalt pavement construction and maintenance, and specifically relates to a polymer asphalt emulsion, a raw material composition thereof, a preparation method thereof and an application thereof. Background Art
[0002] Cold mix cold paving technology is widely used in road maintenance, reinforcement, and renovation projects due to its advantages of convenient construction, low energy consumption, and environmental protection. Conventional anionic polymer emulsions cannot meet the requirements of sufficient mixing operation time and the road specification that the mixing type emulsified asphalt must be cationic (+) charged when used in cold mix cold paving technology. Existing cold mix technology usually uses SBR emulsion (styrene butadiene latex) and SBS (styrene-butadiene-styrene block copolymer) to modify emulsified asphalt.
[0003] However, a large amount of high EO number non-ionic surfactants will be introduced in the process of converting SBR emulsion anions into cationic emulsions. The demulsification process depends on climatic conditions such as the temperature and humidity of the construction site. When the addition ratio is too large, the emulsification will not occur for a long time, and it may even be difficult to form strength. The water damage resistance in the later stage is also not ideal. The SBS modified asphalt emulsification production process has high requirements for modified asphalt production equipment, modified asphalt emulsification equipment and construction equipment, and the modified emulsified asphalt has poor stability, which greatly limits the application scope of SBS modified asphalt emulsification technology. The above problems have led to the cold mix and cold paving process often being unable to open to traffic for a long time after construction, gravel falling off after opening to traffic, and even large-scale peeling in a short period of time.
[0004] The patent application publication number is CN 108530920 A, which discloses a method of adding surfactant-type additives to improve the performance of cold-mixed and cold-paved mixtures. The 2d and 4d splitting strength performance of asphalt mixtures was evaluated, but it is difficult to close traffic for more than two days in actual road maintenance construction, and large doses of surfactants have a greater impact on the mixture's ability to resist water damage.
[0005] The patent application publication number is CN114560966A, which discloses a method for preparing a cationic acrylic emulsion modified by an organosiloxane. The surface activity of the cationic surfactant is weak, and the addition of non-ionic surfactants reduces the water resistance effect. In addition, the operability time of the quaternary ammonium salt emulsifier emulsion after mixing with stone is very short, and the stone compatibility is poor, which cannot meet the mixing construction requirements of cold-mixed and cold-laid asphalt mixtures. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a polymer asphalt emulsion, a raw material composition thereof, and a preparation method and application thereof.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] In one aspect, the present invention provides a raw material composition of a polymer asphalt emulsion, which comprises, by weight:
[0009] 20-100 parts of asphalt, 30-110 parts of polymerizable monomers, 0.1-1 parts of carboxyl monomers, 0.1-2 parts of cross-linking monomers, 0.1-2 parts of functional monomers, 0.2-0.7 parts of initiators, 1.5-4.5 parts of surfactants, 1-6 parts of pH regulators, and 60-80 parts of water.
[0010] In some embodiments, the asphalt is selected from at least one of petroleum-based asphalt, SBS-modified asphalt, SBR-modified asphalt, and SIS-modified asphalt.
[0011] In some embodiments, the polymerizable monomer is selected from at least one of styrene, acrylamide, methyl acrylate, ethyl acrylate, butyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isooctyl methacrylate, isodecyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, cyclohexyl acrylate and cyclohexyl methacrylate. As a further preferred embodiment, the polymerizable monomer does not contain styrene.
[0012] In some embodiments, the carboxyl monomer is selected from at least one of acrylic acid, methacrylic acid, fumaric acid, maleic anhydride, and itaconic acid. As a further preferred embodiment, the carboxyl monomer is methacrylic acid.
[0013] In some embodiments, the crosslinking monomer is selected from at least one of diacetone acrylamide, ethyl acetoacetyl methacrylate, and glycidyl methacrylate. As a further preferred embodiment, the crosslinking monomer is glycidyl methacrylate.
[0014] In some embodiments, the functional monomer is selected from at least one of vinyl triethoxysilane, vinyl trimethoxysilane, and vinyl tri(β-methoxyethoxy)silane. As a further preferred embodiment, the functional monomer is vinyl trimethoxysilane.
[0015] In some embodiments, the initiator is selected from at least one of potassium persulfate, sodium persulfate and ammonium persulfate. As a further preferred embodiment, the initiator is potassium persulfate.
[0016] In some embodiments, the surfactant is selected from at least one of alkylamide, alkyl polyetheramide, alkyl imidazoline, lignin ammonium, alkyl polyoxyethylene ether, and alkylphenol polyoxyethylene ether. As a further preferred embodiment, the surfactant is alkylamide and / or alkyl imidazoline.
[0017] In some embodiments, the pH adjuster is selected from at least one of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, formic acid, and acetic acid. As a further preferred embodiment, the pH adjuster is phosphoric acid.
[0018] In some preferred embodiments, the weight percentage of the asphalt is 30 to 70 parts.
[0019] In some preferred embodiments, the weight percentage of the polymerizable monomer is 50 to 90 parts.
[0020] In some preferred embodiments, the weight percentage of the carboxyl monomer is 0.3 to 0.8 parts.
[0021] In some preferred embodiments, the weight percentage of the cross-linking monomer is 0.2 to 1.7 parts.
[0022] In some preferred embodiments, the weight percentage of the functional monomer is 0.3 to 1.7 parts.
[0023] In some preferred embodiments, the weight portion of the initiator is 0.3 to 0.5 parts.
[0024] In some preferred embodiments, the weight proportion of the surfactant is 2 to 3 parts.
[0025] In some preferred embodiments, the pH adjuster is present in an amount of 2 to 4 parts by weight.
[0026] In some preferred embodiments, the weight percentage of the water is 65 to 75 parts.
[0027] In another aspect, the present invention provides a method for preparing a polymer asphalt emulsion, wherein the raw materials of the polymer asphalt emulsion include the raw material composition of the polymer asphalt emulsion described above, and specifically comprises the following steps:
[0028] (1) uniformly mixing a portion of surfactant, water, polymerizable monomer, carboxyl monomer, crosslinking monomer and pH adjuster to prepare a monomer emulsion;
[0029] (2) adding the remaining surfactant, water and pH adjuster into the reaction container and mixing them evenly to prepare a primer aqueous solution;
[0030] (3) adding a portion of the monomer emulsion to the primer aqueous solution, and then adding a portion of the initiator, stirring, and heating to 80-95° C. for heat preservation;
[0031] (4) taking the remaining initiator and water and mixing them evenly, and simultaneously dropping them into the reaction container with the remaining monomer emulsion, stirring, and after a period of dropping, adding the functional monomer into the monomer emulsion and continuing to drop, the total dropping time is 2.5 to 6 hours, and after the dropping is completed, heat preservation treatment is performed under stirring to obtain a polymer emulsion;
[0032] (5) Cooling the mixture to 45-70° C., adding asphalt to the polymer emulsion under shearing or grinding conditions, continuing shearing or grinding, cooling, and filtering to obtain a polymer asphalt emulsion.
[0033] In step (1), the weight proportion of the part of surfactant is 1.4 to 4.0 parts.
[0034] In step (1), the weight proportion of water is 29 to 35 parts.
[0035] In step (1), the weight portion of the pH adjuster is 0.1 to 0.5 parts.
[0036] In step (2), the weight proportion of the pH adjuster is 0.9 to 5.5 parts.
[0037] In step (1) and step (2), the pH value adjusted by the pH adjuster is in the range of 1 to 7, preferably 2 to 5.
[0038] In step (2), the weight portion of the remaining surfactant is 0.1 to 0.5 parts.
[0039] In step (2), the weight proportion of water is 30 to 40 parts.
[0040] In step (3), the weight proportion of the monomer emulsion is 0 to 5 parts.
[0041] In step (3), the weight portion of the partial initiator is 0.1 to 0.2 parts.
[0042] In step (3), the heat preservation treatment time is 5 to 20 minutes.
[0043] In step (4), the weight portion of the remaining initiator is 0.1 to 0.5 parts.
[0044] In step (4), the weight proportion of water is 1 to 5 parts.
[0045] In step (4), the functional monomer is added 0 to 5 hours after the start of the dropwise addition, preferably 2 to 3 hours after the start of the dropwise addition.
[0046] In step (4), the dropping temperature is 80-95°C.
[0047] In step (4), the heat preservation treatment time is 0.5 to 2 hours.
[0048] In step (4), the temperature of the heat preservation treatment is 80-95°C.
[0049] In step (5), the temperature when the asphalt is added is 110-180°C, preferably 130-160°C.
[0050] In step (5), the time for continuing shearing or grinding is 30 seconds to 30 minutes.
[0051] The third aspect of the present invention provides a polymer asphalt emulsion, which is prepared by the method for preparing the polymer asphalt emulsion as described above.
[0052] The fourth aspect of the present invention provides the use of polymer asphalt emulsion in the cold mix and cold paving process of asphalt pavement.
[0053] The beneficial effects of the present invention are:
[0054] (1) The production process of the polymer asphalt emulsion of the present invention is mild, no waste such as solvent is generated, and it is a water-based emulsion product that can be constructed at room temperature. The ratio of polymer to asphalt in the emulsion can be adjusted over a wide range, and it is easy to produce and use.
[0055] (2) The present invention adds a pH regulator to the polymer primer water and the polymerization monomer emulsion, which can improve the emulsification ability of the surfactant, reduce the amount of emulsifier used, and at the same time improve the reaction activity of the initiator, so that the entire polymerization reaction is faster, the polymerizable monomer reacts more fully, and the polymerization monomer residue is reduced. The cationic (+) charge is beneficial to the charge attraction between the polymer emulsion and the negatively charged stone, which is beneficial to the spreading and adhesion of the polymer particles on the stone surface, and improves the compatibility of the polymer asphalt with the stone.
[0056] (3) The polymer asphalt emulsion of the present invention is weakly acidic, which can inhibit the hydrolysis of the ester group on the polymer chain and promote the amino group or imidazoline group in the surfactant to be in an ionized state, which can stably coexist with the cross-linking group in the polymer. When it comes into contact with a large amount of strong alkaline powder such as cement, mineral powder, stone, etc. during construction, the pH value of the system rises rapidly, catalyzing the cross-linking monomer and the amide or imidazoline group in the surfactant to cross-link, promote the polymer asphalt emulsion to quickly break the emulsion and form strength, improve the early strength of the mixture, and reduce the road maintenance and traffic closure time. The carboxyl group forms ionic bonds with divalent metal ions such as calcium ions and magnesium ions in the filler to increase the viscosity of the emulsified asphalt mortar, thereby increasing the single-layer construction thickness and increasing the thickness of the asphalt film on the surface of the upper stone, so that the surface stone adheres more firmly after the mixture is formed and is not easy to fall off.
[0057] (4) The introduction of functional monomers into the polymer emulsion of the present invention can improve the adhesion between the polymer asphalt particles and inorganic materials such as stones, improve the water damage resistance of the asphalt mixture, and reduce the wet wheel wear value of the asphalt mixture, thereby increasing the service life of the road surface. The functional monomers are added after the polymer has reacted for a certain period of time, which can cause them to be mainly distributed on the surface of the polymer particles, thereby improving the reaction efficiency of the functional monomers with inorganic materials such as stones.
[0058] (5) In conventional polymer-bitumen emulsion modified mixing, polymer particles and asphalt particles are independently distributed in the water column. After demulsification and film formation, only micron-level mixing can be achieved between different phase interfaces. The surfactant used in the polymer emulsion is very different from the surfactant used in the asphalt emulsion. After the two are mixed, on the one hand, it will affect the stability of the emulsion, and on the other hand, it will seriously interfere with the mixing time, especially when the two are mixed in a large proportion. The present invention uses polymer emulsion to directly emulsify asphalt to form a polymer asphalt emulsion, so that the polymer particles are more fully and evenly distributed inside and outside the asphalt particles. After demulsification and film formation, nano-level mixing is achieved at the phase interface, which greatly improves the uniformity of dispersion and avoids the segregation of the two due to density difference. In addition, the polymer and asphalt can be adjusted in large proportions. After the polymer asphalt emulsion is demulsified and formed, the soft and hard monomers of the polymer improve the low-temperature and high-temperature properties of the asphalt and expand its scope of application. The cross-linking monomer forms a spatial interpenetrating cross-linking network inside the asphalt binder, which limits the fluidity of the asphalt and improves the ability of the asphalt mixture to resist deformation, thereby improving the anti-rutting performance of the asphalt mixture. DETAILED DESCRIPTION
[0059] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications. In addition, the reagents and raw materials used in the present invention are all commercially available.
[0060] Example 1
[0061] 3 parts of C500 surfactant (alkylamide, Nouryon) and 1 part of AEO-9 (Haian Petrochemical), 30 parts of water, 50 parts of butyl acrylate (BA), 28 parts of 2-ethylhexyl acrylate (2-EHA), 30 parts of styrene (St), 2 parts of acrylamide (AM), 0.1 parts of acrylic acid (AA), 1.8 parts of diacetone acrylamide (DAAM), 5.5 parts of 20% hydrochloric acid were fully mixed to form a monomer emulsion with a pH value of 1.6;
[0062] Take 0.5 parts of C500, 0.5 parts of 20% hydrochloric acid, and 36 parts of water and add them into a reaction vessel, start stirring, and prepare a primer aqueous solution with a pH value of 1.8;
[0063] Raise the temperature to 87°C, add 1 part of the monomer emulsion to the reaction vessel, add 0.2 parts of sodium persulfate (SPS), and keep warm for 15 minutes;
[0064] Take 0.5 parts of sodium persulfate (SPS) and 5 parts of water and mix them evenly, and add them dropwise into the reaction container together with the remaining monomer emulsion. When the addition is continued for 2 hours, add 0.2 parts of A151 (vinyl triethoxysilane, Union Carbide Corporation, USA) into the monomer emulsion and stir evenly. The monomer emulsion is added dropwise within 6 hours. During the addition, the temperature in the reaction container is controlled at 82±1°C. After the addition is completed, keep warm for 1 hour.
[0065] Cool to 50°C, add 20 parts of 135°C Zhenhai 70# base asphalt, shear at 2800rpm for 1min, cool to room temperature and filter to obtain polymer asphalt emulsion. See Table 1 for specific ratios.
[0066] Table 1
[0067]
[0068]
[0069] Application Example 1
[0070] Test Example 1: The ionic charge and solid content of the polymer asphalt emulsion are obtained; 100 parts of basalt rock produced in Tianchang, Anhui Province, which meets the MS-III standard, are taken, 1 part of "Conch Brand" ordinary silicate 42.5# cement, 3 parts of water, and 11 parts of polymer asphalt emulsion are added, the mixture is quickly mixed and timed, and the mixing time, cohesion, wet wheel wear and rutting depth change rate are tested.
[0071] Example 2
[0072] The surfactant in Example 1 was replaced by L-5 (lignin amine, Shengquan Company) and OP-10 (alkylphenol polyoxyethylene ether, Haian Petrochemical), 20% hydrochloric acid was replaced by 85% formic acid, acrylic acid monomer was replaced by fumaric acid, the pH value of the monomer emulsion was 4.5, and the pH value of the primer aqueous solution was 2.9; the monomer emulsion addition time was changed to 4.8h, and the temperature in the reaction vessel was controlled at 84±1°C during the addition process, and the asphalt addition temperature was controlled at 145°C. See Table 2 for detailed proportions. Application Example 2 is the same as Application Example 1.
[0073] Table 2
[0074]
[0075]
[0076] Example 3
[0077] The surfactant 2 in Example 1 was replaced by S-90 (alkyl polyoxyethylene ether, SECCO), 20% hydrochloric acid was replaced by glacial acetic acid, acrylic acid monomer was replaced by maleic anhydride, the pH value of the monomer emulsion was 5.5, and the pH value of the primer aqueous solution was 3.3; the monomer emulsion addition time was changed to 4 hours, and the temperature in the reaction container was controlled at 86±1°C during the addition process, and the asphalt addition temperature was controlled at 150°C. See Table 3 for detailed proportions. Application Example 3 is the same as Application Example 1.
[0078] Table 3
[0079]
[0080]
[0081] Example 4
[0082] The surfactant 2 in Example 1 is replaced by TO-8 (alkyl polyether, Yangzi-BASF Company), 20% hydrochloric acid is replaced by 16% nitric acid, acrylic acid monomer is replaced by itaconic acid, the pH value of the monomer emulsion is 2.3, and the pH value of the primer aqueous solution is 1.8; the monomer emulsion addition time is changed to 3.5h, and the temperature in the reaction container is controlled at 88±1°C during the addition process, and the asphalt addition temperature is controlled at 158°C. See Table 4 for detailed proportions. Application Example 4 is the same as Application Example 1.
[0083] Table 4
[0084]
[0085]
[0086] Example 5
[0087] The surfactant in Example 1 was replaced by Perel417 (alkyl imidazoline, Ingevity Corporation) and 1309 (alkyl polyether, Corelink Corporation), 20% hydrochloric acid was replaced by 15% phosphoric acid, acrylic acid monomer was replaced by methacrylic acid, A151 was replaced by A171, initiator SPS was replaced by KPS (potassium persulfate), pH value of monomer emulsion was 2.8, pH value of primer aqueous solution was 1.7; monomer emulsion addition time was changed to 4.5h, temperature in reaction vessel was controlled at 86±1°C during addition, temperature of asphalt addition was controlled at 138°C, detailed proportions were shown in Table 5, Application Example 4 is the same as Application Example 1.
[0088] Table 5
[0089]
[0090]
[0091] Example 6
[0092] The surfactant in Example 1 was replaced by MQK-1M (alkyl amide, Ingevity) and LCN070 (alkyl polyether, Clariant), 20% hydrochloric acid was replaced by 15% phosphoric acid, acrylic acid monomer was replaced by methacrylic acid, A151 was replaced by A171, initiator SPS was replaced by KPS (potassium persulfate), the pH value of the monomer emulsion was 3.6, and the pH value of the primer aqueous solution was 2.6; the monomer emulsion addition time was changed to 4.5h, and the temperature in the reaction vessel was controlled at 86±1°C during the addition process, and the asphalt addition temperature was controlled at 150°C. See Table 6 for detailed proportions. Application Example 6 is the same as Application Example 1.
[0093] Table 6
[0094]
[0095]
[0096] Example 7
[0097] The surfactant in Example 1 was replaced by W-5 (a mixture of lignin amine and alkyl polyoxyethylene ether, Ingevity Corporation), 20% hydrochloric acid was replaced by 10% sulfuric acid, the initiator SPS was replaced by APS (ammonium persulfate), the pH value of the monomer emulsion was 1.6, and the pH value of the primer aqueous solution was 1.4; the monomer emulsion addition time was changed to 4.5h, and the temperature in the reaction vessel was controlled at 89±1°C during the addition process, and the asphalt addition temperature was controlled at 160°C. See Table 7 for detailed proportions. Application Example 7 is the same as Application Example 1.
[0098] Table 7
[0099]
[0100]
[0101] Example 8
[0102] The surfactant 2 in Example 1 is replaced by 1309 (alkyl polyoxyethylene ether, Xinlian Company), the initiator SPS is replaced by APS (ammonium persulfate), the pH value of the monomer emulsion is 4.2, and the pH value of the primer aqueous solution is 1.9; the monomer emulsion addition time is changed to 3.5h, and the temperature in the reaction container is controlled at 91±1°C during the addition process, and the asphalt addition temperature is controlled at 160°C. See Table 8 for detailed proportions. Application Example 8 is the same as Application Example 1.
[0103] Table 8
[0104]
[0105]
[0106] Example 9
[0107] The surfactant in Example 1 was replaced with EM-520S (alkyl polyether amide, Longfu material), the pH value of the monomer emulsion was 5.3, and the pH value of the primer aqueous solution was 2.5; the monomer emulsion addition time was changed to 2.5h, and the temperature in the reaction vessel was controlled at 94±1°C during the addition process, and the asphalt addition temperature was controlled at 160°C. For detailed proportions, see Table 9. Application Example 9 is the same as Application Example 1.
[0108] Table 9
[0109]
[0110]
[0111] Comparative Example 1
[0112] The only difference from Example 1 is that the cross-linking monomer DAAM (diacetone acrylamide) in Example 1 is replaced with deionized water, and the other conditions are the same as Example 1 and Application Example 1.
[0113] Comparative Example 2
[0114] The polymer asphalt emulsion prepared in Example 1 was replaced with a commercially available anionic nonionic acrylic polymer emulsion and mixed evenly with a commercially available 60% solid content road mixing type emulsified asphalt. The application of comparative example 2 was consistent with that of application example 1.
[0115] Comparative Example 3
[0116] The polymer modified emulsified asphalt prepared in Application Example 1 was changed to a commercially available 60% solid content mixing type modified emulsified asphalt, wherein the asphalt was modified with 3.8% SBS, and the other conditions were the same as those in Application Example 1.
[0117] Comparative Example 4
[0118] The polymer modified emulsified asphalt prepared in Application Example 1 was changed to a commercially available 60% solid content mixing type emulsified asphalt (BCR), which contained 4.0% SBR latex. The other conditions were the same as those in Application Example 1.
[0119] Comparative Example 5
[0120] The polymer modified emulsified asphalt prepared in Example 1 was changed to a commercially available 60% solid content mixing type emulsified asphalt (BCR), to which 6.0% of commercially available SBS latex was added, and the other conditions were the same as those in Application Example 1.
[0121] Comparative Example 6
[0122] The only difference from Example 1 is that the functional monomer A151 in Example 1 is replaced with deionized water, and the other conditions are the same as Example 1 and Application Example 1.
[0123] Comparative Example 7
[0124] The only difference from Example 1 is that the 20% hydrochloric acid in the primer aqueous solution and the monomer emulsion in Example 1 is replaced with deionized water so that the pH value of the primer water and the monomer emulsion is greater than 7 (alkylamide alkalinity). The other conditions are the same as Example 1 and Application Example 1.
[0125] Comparative Example 8
[0126] The only difference from Example 1 is that the amount of 20% hydrochloric acid in Example 1 is increased from 6 parts to 7.5 parts, the pH values of the primer aqueous solution and the monomer emulsion are both less than 1, and the other conditions are the same as Example 1 and Application Example 1.
[0127] Product performance testing
[0128] The above application example test method is tested with reference to JTG 5142-2019 "Technical Specifications for Highway Asphalt Pavement Maintenance", JTGF40-2004 "Technical Specifications for Highway Asphalt Pavement Construction", JTG E20-2019 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", and other relevant technical specifications or standards, among which:
[0129] The mixing time test is used to evaluate the shortest construction time of cold mix and cold paving asphalt mixture, which is required to be no less than 120s;
[0130] The cohesion test is used to evaluate the shortest time required for closed traffic maintenance after the construction of cold-mixed cold-paved asphalt mixture. The cohesion value is required to be ≥ 2.0 N·m after 60 minutes. For the same maintenance time, the greater the cohesion value, the shorter the required maintenance time.
[0131] The wet wheel abrasion test is used to evaluate the water damage resistance and compatibility of cold mix cold paved asphalt mixture. The smaller the abrasion value, the better the water damage resistance and compatibility, and the longer the service life of the cold mix asphalt mixture.
[0132] The rutting depth rate test is used to evaluate the rutting resistance of cold-mixed and cold-paved asphalt mixtures. The smaller the rutting depth rate, the stronger the ability to resist rutting deformation.
[0133] Table 10
[0134]
[0135]
[0136] It can be seen from Table 10 that the polymer asphalt emulsion produced in the embodiment of the present invention is applied to cold-mix cold-paving asphalt mixture. While the mixing construction time is longer than that of the control example, the cohesion after curing for 1 hour is much greater than that of the control example, and the wet wheel wear value and rutting depth rate are also significantly better than those of the control example. Various performances are relatively balanced.
[0137] Finally, it should be noted that in the present invention, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method, article or apparatus.
[0138] Although the present disclosure has been disclosed above through the description of the specific embodiments of the present disclosure, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present disclosure within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present disclosure.
Claims
1. A raw material composition of a polymer asphalt emulsion, characterized in that: In parts by weight, it includes: 20-100 parts of asphalt, 30-110 parts of polymerizable monomers, 0.1-1 parts of carboxyl monomers, 0.1-2 parts of cross-linking monomers, 0.1-2 parts of functional monomers, 0.2-0.7 parts of initiators, 1.5-4.5 parts of surfactants, 1-6 parts of pH regulators, and 60-80 parts of water.
2. The raw material composition of polymer asphalt emulsion according to claim 1, characterized in that: The asphalt is selected from at least one of petroleum-based asphalt, SBS modified asphalt, SBR modified asphalt, and SIS modified asphalt; And / or, the polymerizable monomer is selected from at least one of styrene, acrylamide, methyl acrylate, ethyl acrylate, butyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isooctyl methacrylate, isodecyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, cyclohexyl acrylate and cyclohexyl methacrylate, and preferably, the polymerizable monomer does not contain styrene; And / or, the carboxyl monomer is selected from at least one of acrylic acid, methacrylic acid, fumaric acid, maleic anhydride and itaconic acid, preferably methacrylic acid; And / or, the cross-linking monomer is selected from at least one of diacetone acrylamide, ethyl acetoacetyl methacrylate, and glycidyl methacrylate, preferably glycidyl methacrylate; And / or, the functional monomer is selected from at least one of vinyl triethoxysilane, vinyl trimethoxysilane, and vinyl tri(β-methoxyethoxy)silane, preferably vinyl trimethoxysilane; And / or, the initiator is selected from at least one of potassium persulfate, sodium persulfate and ammonium persulfate, preferably potassium persulfate; And / or, the surfactant is selected from at least one of alkylamide, alkyl polyetheramide, alkyl imidazoline, lignin ammonium, alkyl polyoxyethylene ether, and alkylphenol polyoxyethylene ether, preferably alkylamide and / or alkyl imidazoline; And / or, the pH adjuster is selected from at least one of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, formic acid and acetic acid, preferably phosphoric acid.
3. The raw material composition of the polymer asphalt emulsion according to any one of claims 1 to 2, characterized in that The weight proportion of the asphalt is 30 to 70 parts; And / or, the weight proportion of the polymerizable monomer is 50 to 90 parts; and / or, the weight portion of the carboxyl monomer is 0.3 to 0.8 parts; and / or, the weight proportion of the cross-linking monomer is 0.2 to 1.7 parts; And / or, the weight proportion of the functional monomer is 0.3 to 1.7 parts; And / or, the weight portion of the initiator is 0.3 to 0.5 parts; And / or, the weight proportion of the surfactant is 2 to 3 parts; And / or, the weight portion of the pH adjuster is 2 to 4 parts; And / or, the weight proportion of the water is 65 to 75 parts.
4. A method for preparing a polymer asphalt emulsion, characterized in that: The raw material of the polymer asphalt emulsion comprises the raw material composition of the polymer asphalt emulsion according to any one of claims 1 to 3, and specifically comprises the following steps: (1) uniformly mixing a portion of surfactant, water, polymerizable monomer, carboxyl monomer, crosslinking monomer and pH adjuster to prepare a monomer emulsion; (2) adding the remaining surfactant, water and pH adjuster into the reaction container and mixing them evenly to prepare a primer aqueous solution; (3) adding a portion of the monomer emulsion to the primer aqueous solution, and then adding a portion of the initiator, stirring, and heating to 80-95° C. for heat preservation; (4) taking the remaining initiator and water and mixing them evenly, and simultaneously dropping them into the reaction container with the remaining monomer emulsion, stirring, and after a period of dropping, adding the functional monomer into the monomer emulsion and continuing to drop, the total dropping time is 2.5 to 6 hours, and after the dropping is completed, heat preservation treatment is performed under stirring to obtain a polymer emulsion; (5) Cooling the mixture to 45-70° C., adding asphalt to the polymer emulsion under shearing or grinding conditions, continuing shearing or grinding, cooling, and filtering to obtain a polymer asphalt emulsion.
5. The method for preparing the polymer asphalt emulsion according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: In step (1), the weight proportion of the part of surfactant is 1.4 to 4.0 parts; In step (1), the weight parts of water are 29 to 35 parts; In step (1), the weight portion of the pH adjuster is 0.1 to 0.5 parts; In step (2), the weight proportion of the pH adjuster is 0.9 to 5.5 parts; In step (1) and step (2), the pH value adjusted by the pH adjuster is in the range of 1 to 7, preferably 2 to 5; In step (2), the weight portion of the remaining surfactant is 0.1 to 0.5 parts; In step (2), the weight proportion of water is 30 to 40 parts.
6. The method for preparing the polymer asphalt emulsion according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: In step (3), the weight proportion of the monomer emulsion is 0 to 5 parts; In step (3), the weight portion of the initiator is 0.1 to 0.2 parts; In step (3), the heat preservation treatment time is 5 to 20 minutes.
7. The method for preparing the polymer asphalt emulsion according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: In step (4), the weight portion of the remaining initiator is 0.1 to 0.5 parts; In step (4), the weight proportion of water is 1 to 5 parts; In step (4), the functional monomer is added 0 to 5 hours after the start of the dropwise addition, preferably 2 to 3 hours after the start of the dropwise addition; In step (4), the dropping temperature is 80 to 95° C.; In step (4), the heat preservation treatment time is 0.5 to 2 hours; In step (4), the temperature of the heat preservation treatment is 80-95°C.
8. The method for preparing a polymer asphalt emulsion according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: In step (5), the temperature of the asphalt when added is 110 to 180° C., preferably 130 to 160° C.; In step (5), the time for continuing shearing or grinding is 30 seconds to 30 minutes.
9. A polymer asphalt emulsion, characterized in that: The polymer asphalt emulsion is prepared by the preparation method of the polymer asphalt emulsion according to any one of claims 4 to 8.
10. Use of the polymer asphalt emulsion as claimed in claim 9 in a cold mix and cold paving process for asphalt pavement.
Citation Information
Patent Citations
Additive for cold mixing and cold spreading of emulsified asphalt as well as preparation method and application of additive
CN108530920A
Preparation of organosiloxane modified cationic acrylic emulsion
CN114560966A
Polymer latex resin and preparation method and application thereof
CN109970901A
Water-based polyacrylate emulsion as well as preparation method and application method thereof
CN110330853A
Acrylic emulsion for road and bridge asphalt waterproof material as well as preparation method and application of acrylic emulsion
CN116396425A
Cited By
Polymer asphalt emulsion, and raw material composition thereof, preparation method therefor and use thereof
WO2026152732A1